STRATEGI PEMASARAN ADIDAS ORIGINALS MELALUI INSTAGRAM UNTUK MENINGKATKAN MINAT BELI KONSUMEN - Wibowo, Ardy Suwito; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
Instagram is a marketing tool that is popularly used in the creative industries. Adidas has been using this tool because of Instagram’s wide coverages and cheap marketing costs. Currently, Adidas ranks second in terms of sales. Adidas’ strategy to overcome this sales problem is through Adidas Originals. This research aims to test the variables’ influences of social media marketing perception, visual communication perception, and celebrity endorser perception towards consumer's buying interest using online word of mouth as the intervening variable. This study focuses on consumers who recognise Adidas Originals, have an Instagram account and follow @adidasoriginals in Semarang. This research employs a purposive sampling technique on 100 respondents. The method used is Structural Equation Model with AMOS 22.0 Software.The results in this research show that social media marketing perception, visual communication  perception,  and  celebrity  endorser  perception  have  positively  and significantly influenced the intervening variable, which is online word of mouth. While online word of mouth has positively and significantly influenced consumer's buying interest.